2020
DOI: 10.1002/chem.201905524
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide Based Nanomaterials for Rechargeable Batteries

Abstract: The rapid development of electrochemical energy storage systems requires new electrode materials with high performance. As at wo-dimensional material, molybdenum disulfide (MoS 2 )h as attracted increasing interest in energy storage applications due to its layered structure, tunable physical and chemical properties,a nd high capacity.I nt his review,t he atomic structuresa nd properties of different phases of MoS 2 are first introduced. Then, typical synthetic methods for MoS 2 and MoS 2 -basedc omposites are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 157 publications
0
17
0
Order By: Relevance
“…[6,7] 2D layered materials, molybdenum disulfide (MoS 2 ) is one of the most promising candidates for PIBs due to its graphene-like layered structure, low cost, wide interlayer spacing (≈6.15 Å for 2H phase), and high theoretical capacity. [8][9][10][11][12] However, for commercial MoS 2 powder, the reversible capacity is relatively low (≈65 mAh g −1 at 20 mA g −1 ). [6] According to the study of Wu and co-workers during the K + intercalation process, a hexagonal K 0.4 MoS 2 compound was formed.…”
Section: In This Work the 1t/2h-phase Hybrid Mos 2 Nanosheets Are Sumentioning
confidence: 99%
“…[6,7] 2D layered materials, molybdenum disulfide (MoS 2 ) is one of the most promising candidates for PIBs due to its graphene-like layered structure, low cost, wide interlayer spacing (≈6.15 Å for 2H phase), and high theoretical capacity. [8][9][10][11][12] However, for commercial MoS 2 powder, the reversible capacity is relatively low (≈65 mAh g −1 at 20 mA g −1 ). [6] According to the study of Wu and co-workers during the K + intercalation process, a hexagonal K 0.4 MoS 2 compound was formed.…”
Section: In This Work the 1t/2h-phase Hybrid Mos 2 Nanosheets Are Sumentioning
confidence: 99%
“…2D nanomaterials have shown great prospects in various research fields including energy storage, catalysis, sensing, electronics, etc. [122][123][124] DESs are known as green solvents having the advantages of nonflammability, high polarity, negligible vapor pressure, and easy recycling, and thus have been used as exfoliation agent to prepare single-or few-layer 2D materials. Abdelkader et al reported the use of ChCl/urea system to mechanochemically exfoliate 2D crystals, including graphite, boron nitride, and transition metal dichalcogenides.…”
Section: Dess As Exfoliation Agents For Nanomaterialsmentioning
confidence: 99%
“…These layered structures facilitate the transport of various carriers and can also adapt to the volume change during ion insertion. Because of their different chemical composition and unique crystal structure, as well as the fact that the d-orbitals can be filled with different elements, TMDs can be used as functional materials for electronic insulation, semiconductors, and superconductivity [ 27 ].…”
Section: Characterization and Synthetic Methods Of Tmdmentioning
confidence: 99%